PELAKSAANAAN KEGIATAN CSR â€œKAWAN RAMADHANâ€ OLEH CORPORATE COMMUNICATION DEPARTEMENT PT JIEP - Maulizal, Achmad (Universitas Bina Sarana Informatika, 2017)
Corporate Social Responsibilities or CSR has been the attention in many corporation. To tackle variety of CSR engagement, corporation needs one specific unit to effectively manages all the activities. One of the unit design to handle CSR is Corporate Communication Department. As in PT Jakarta Industrial Estate Pulogadung (JIEP) thant manages Pulogadung Industrial Estate, the Corporate Communication Department run the â€œKawan Ramadhanâ€ a CSR activitity targeted to surrounding community of Pulogadung Industrial Estate in Ramadhan month 2017. This journal try to see how the event was implemented by PT JIEP Corporate Communication Department. Â Keywords: Corporate Communication, Corporate Social Responsibilities